A Study On The Potential Of Peltier In Generating Electricity Using Heat Loss At Engine And Exhaust Vehicle - Mohd Annuar, Khalil Azha; Harun, Mohamad Haniff; Nor Azmi, Muhammad Wahyuddin; Mohd Aras, Mohd Shahrieel; Azlan, Umar Al-Amani; Azahar, Arman Hadi; Mohd Ab Halim, Mohd Firdaus; Yaakub, Muhamad Faizal; Zainal Abidin, Amar Faiz (Penerbit Akademia Baru, 2018)
In the era of globalization, the electrical energy supply is the main priority in order to do our jobs and daily activities.Unfortunately,limited power supply for the electrical energy usage makes it hard to continuously provide electrical energy for 24 hours.By using Peltier device,it is possible to develop a portable generating system using heat loss in machines and vehicles.The generating system theoretically can harness the heat loss to produce additional electricity for other usage. The objective of the generating system is to study on the potential of Peltier device to generate useful electricity for additional power supply using heat loss. This generating system can be applied on many types of machines and other type of mechanism such as vehicle that release heat loss.In this project,the generating system is evaluated based on the magnitude of voltage output, and it is found that the system shows higher efficiency at 12.59% by using the proposed heat sink.